Towards a surveillant reality in tennis - Papageorgiou, Konstantinos; Lekkas, Demetrios (Epistēmēs Metron Logos, 2023)
Here we attempt to present an application of epistemologically significant concepts that have already been described in depth in previous works. First and foremost, we refer to the dual paired method(s) of epistēmē, which is critically different from the scientific method due to a very common misconception ubiquitous among scholars and academics al over; but we also refer to surveillance, theory and truth, as well as the two new, save relevant, concepts of surveillant reality and experiential reality. The example is taken from tennis, a field to which one of the authors regularly contributes. We shall attempt to explore the ways in which the dual paired method of epistēmē is applied to sports science (in tennis) and, based on that, to clarify the concept and the differences between surveillant reality and experiential reality.